2015
DOI: 10.1519/jsc.0000000000000905
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Kinetics, Kinematics, and Electromyography During Single-Leg Assisted and Unassisted Cycling

Abstract: To use single-leg cycling training for varying populations, it is important to understand whether a counterweight attached to the contralateral crank during single-leg cycling drills replicates the effects of the opposite leg in the ipsilateral leg. Therefore, we compared single-leg assisted cycling using a counterweight on the contralateral crank for joint kinetics, kinematics, and lower-limb muscle activation. Fourteen healthy nonathletes performed 2 bilateral cycling trials (240 ± 23 W and 90 ± 2 rpm) and 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 26 publications
3
11
0
2
Order By: Relevance
“…During the single-leg intervals a specially designed counterweight (10 kg) was attached to the opposite pedal to allow a fluid pedaling motion. Previous research has successfully used this method in both healthy and clinical populations (3,5,(21)(22)(23)(24) and has shown that counterweighted single-leg cycling is more similar to double-leg cycling when compared with unassisted single-leg cycling (3,21).…”
Section: Methodsmentioning
confidence: 99%
“…During the single-leg intervals a specially designed counterweight (10 kg) was attached to the opposite pedal to allow a fluid pedaling motion. Previous research has successfully used this method in both healthy and clinical populations (3,5,(21)(22)(23)(24) and has shown that counterweighted single-leg cycling is more similar to double-leg cycling when compared with unassisted single-leg cycling (3,21).…”
Section: Methodsmentioning
confidence: 99%
“…; Bini et al . ). There is no evidence to suggest that mitochondrial adaptations to single‐leg cycling transfer to the non‐exercising leg, meaning that the contralateral limb can be trained in a different manner or serve as a non‐exercise control (Saltin et al .…”
Section: Introductionmentioning
confidence: 97%
“…To collect kinematic athletes' clearance data, twenty markers were attached to the body of each participant for digitization. Body markers, using the Hanavan model modified by De Leva (1996), were digitized using the video-based data analysis system SkillSpector ® 1.3.2 [Odense SØ -Denmark], (Bini, Jacques, Lanferdini, & Vaz, 2015;Lanferdini et al, 2016;Mkaouer, 2018;Mkaouer, Chaabene, Amara, Negra, & Jemni, 2018;Mkaouer, Jemni, Amara, Chaabène, & Tabka, 2013). Similarly, the body segments' COM was computed using the Hanavan model modified by De Leva (1996).…”
Section: Methodsmentioning
confidence: 99%